Cantora : Mercedes Sosa, the voice of Latin America - Fernández Nitsche, Melisa (Alfred A. Knopf, 2023)
"A picture book about the Latin American folk singer, Mercedes Sosa. Mercedes performed the world over, sharing stories through song. But not everyone loved her singing: a military dictatorship ruled over Argentina, and they saw the power of her voice. Even from exile, Mercedes Sosa was a beacon of freedom for her people, and when she returned to her homeland, she persisted in her work: to be the voice of the voiceless"--